Nomenclature and semantic descriptions of ulcerative and inflammatory lesions seen in Crohn's disease in small bowel capsule endoscopy: An international Delphi consensus statement. Issue 1 (1st February 2020) - Leenhardt, Romain; Buisson, Anthony; Bourreille, Arnaud; Marteau, Philippe; Koulaouzidis, Anastasios; Li, Cynthia; Keuchel, Martin; Rondonotti, Emmanuele; Toth, Ervin; Plevris, John N; Eliakim, Rami; Rosa, Bruno; et al.
Abstract : Background: In the medical literature, the nomenclature and descriptions (ND) of small bowel (SB) ulcerative and inflammatory (U‐I) lesions in capsule endoscopy (CE) are scarce and inconsistent. Inter‐observer variability in interpreting these findings remains a major limitation in the assessment of the severity of mucosal lesions, which can impact negatively on clinical care, training and research on SB‐CE. Objective: Focusing on SB‐CE in Crohn's disease (CD), our aim is to establish a consensus on the ND of U‐I lesions. Methods: An international panel of experienced SB‐CE readers was formed during the 2016 United European Gastroenterology Week meeting. A core group of five CE and inflammatory bowel disease (IBD) experts established an Internet‐based, three‐round Delphi consensus but did not participate in the voting process. The core group built illustrated questionnaires, including SB‐CE still frames of U‐I lesions from patients with documented CD. Twenty‐seven other experts were asked to rate and comment on the different proposals for the ND of the most frequent SB U‐I lesions. For each round, we used a 6‐point rating scale (varying from 'strongly disagree' to 'strongly agree'). The consensus was reached when at least 80 % of the voting members scored the statement within the 'agree' or 'strongly agree' categories. Results: A 100% participation rate was obtained for all the rounds. Consensual ND were reached for the following seven U‐I lesions: aphthoid erosion, deep ulceration, superficial ulceration, stenosis, edema, hyperemia and denudation . Conclusion: Considering the most frequent SB U‐I lesions seen in CE in CD, a consensual ND was reached by the international group of experts. These descriptions and names are useful not only for daily practice and medical education, but also for medical research.